(untitled) (Medical Forum Monthly, 2024)
Objective: Camellia sinensis as a tea (hot decoction) is so widely used throughout the Asia. Therefore to find out, their effects on all the body functions are the need of hour. In the current study the effect of Camellia sinensis on human (females) blood pressure has been evaluated. Study Design: Observational study. Place of Study: This study was conducted at Pharmacy Department, University of Malakand. Materials and Methods: The blood pressure before and after giving the decoction of Camellia sinensis to seventy six individuals was evaluated by using sphygmomanometer and stethoscope. Results: A moderate increase in the blood pressure had been noted. Also a great decrease in the heart rate of individuals has been identified after taking the decoction. Conclusion: From the current study it can be concluded that green tea have an effect of increasing blood pressure in the females, so the heart patients have to take care while using green tea in excess quantity.